Exclusion services in smart city knowledge portal - Marciniak, Katarzyna Iwona; Owoc, Mieczysław Lech (Business Informatics, 2015)
Exclusion phenomenon denotes processes in which some group of people or individuals is permanently blocked from resources (mostly considered as social exclusion). The discussed phenomenon can be considered in many aspects: identifying exclusion as a process, multidimensional research in this area and presenting solutions useful in solving problems. Real support of the processes in overtaking exclusion phenomenon can be offered from Information and Communication Technologies area. The aim of this paper is the presentation of smart city portals content in order to support services devoted to exclusion processes neutralization. Several existing portals of selected smart cities are taken into account. The contents of the research sample will be analysed to investigate the state of the art solutions in the area and confronted with the concept of knowledge portal. The paper consists of five parts, including Introduction and Conclusions. The three merit parts describe exclusion phenomena, then general concept of knowledge portal devoted to services is presented and the last part demonstrates existing solutions in this area
Informatyka Ekonomiczna = Business Informatics, 2015, Nr 2 (36), s. 19-33
Keywords: smart city; exclusion phenomena; knowledge portal; open services; wykluczenie społeczne; portale wiedzy; usługi otwarte